Efektivitas Resusitasi Jantung Paru Terhadap Return Of Spontaneous Circulation Pada Pasien Henti Jantung Di IGD Rumah Sakit X - Aldila Setyari Lestari; Ricky Riyanto Iksan; Rima Berlian Putri (Borneo Nursing Journal (BNJ), 2026)
Cardiopulmonary Resuscitation (CPR) is a critical step that determines the success of rescuing cardiac arrest patients, especially in achieving Return of Spontaneous Circulation (ROSC). Purpose: This National CPR (National CPR) study aims to determine the effectiveness of training interventions on improving nurses' skills in performing CPR according to SOPs for cardiac arrest patients in the Emergency Department (ER). Method: The National CPR study used a quasi-experimental approach with a pre-test and post-test with a control group design. The study sample consisted of an intervention group and a control group, each of which had their CPR skills assessed using an observation sheet. Data analysis was performed using an Independent Sample t-test to determine differences in effectiveness between groups. Results: The effectiveness test showed a significant difference between the intervention and control groups with a p-value of 0.022 (<0.05). The mean score of the intervention group was 1.00, better than the control group at 1.75, indicating that the intervention was effective in improving nurses' skills in performing CPR according to SOPs. Conclusion: CPR has been proven effective in improving nurses' skills in the ER in performing CPR appropriately and according to standards.